Yield Stress Distribution in the Natural Surface Layer of Polycrystals - Starzyński, G.; Gambin, W. (Engineering Transactions, 1996)
A metal surface layer of 2-3 grain diameters thick, before any technological treatment, without residual stresses and with a morphological structure the same as in the hulk material, is called the natural surface layer. Numerous tension tests with metal specimens demonstrate an earlier plastic yield of this layer [1-7]. The phenomenon may have an influence on the hardening and residual stress formation in metal surface layers during technological treatments of tools and machine elements. In the paper, a simple model of a yield stress distribution in the natural surface layer is proposed. The model is based on the fact that dislocation barriers on the free surface of grains are weaker than those on the grain boundaries in the hulk material. According to the model, the yield point in the layer may be 30 % lower than in the hulk material. It enables us to explain the influence of the natural surface layer on the Young modulus measurements for thin metal specimens. The numerical calculations based on the proposed model are in agreement with the experimental observations [10-11].